Special issue introduction Ownership in a post‐aid effectiveness era: Comparative perspectives. (6th April 2020) - Keijzer, Niels; Black, David
Abstract: Motivation: Close to 15 years have passed since the adoption of the Paris Declaration on Aid Effectiveness, which generated unprecedented efforts to advance effective development co‐operation with a central focus on developing country ownership. Under today's international development co‐operation realities, involving inclusive agendas, strategic divergence and increasing competition, discussions on ownership, harmonization and alignment have lost traction. Yet the practices of development co‐operation relationships show strong continuities. Purpose: This special issue examines how the principle of ownership may be understood and advanced under these new conditions. National ownership is prioritized in the 2030 Agenda for Sustainable Development yet has so far been marginalized by a predominantly piecemeal response and by the rise of "mutual benefit" co‐operation. Approach and Methods: This special issue takes an inductive approach to studying specific cases and actors bearing on the challenge of understanding and advancing ownership today, in order to inform future policy and research. The contributions to this special issue mainly draw from qualitative research designs that present detailed research inquiries into specific country and actor cases, drawing from interviews, structured desk reviews of policy documents and the rich body of literature on development effectiveness. They are complemented by two contributions that respectively present quantitative research and probe the critical and post‐development literature for additional insights. Findings: Findings point to an increasing prevalence of pragmatism and self‐interest among all actors, to the detriment of national ownership. Broad co‐operation agendas, a sense of urgency interpreted as a search for quick results, and more diverse, interest‐ and outcome‐driven forms of multi‐stakeholder partnerships all entail a more assertive and proactive approach on the part of external actors. Under these conditions, local initiative may either become stifled or be reasoned away. Given this, today's dominant approaches to co‐operation raise concerns about their ethics and sustainability. Policy implications: Ownership remains both a requirement and a desired outcome of international co‐operation and is key to the effective use of public funding. A key requirement to revitalizing the debate on and practice of ownership is to gather better evidence as the basis for informed scrutiny. To this end, policy‐makers need to reprioritize independent evaluation at both the individual and collective level.